A DC Motor Speed Control For Two Wheeled Vehicles With PWM - Beni Satria; Hermansyah Alam; Erpandi D; Amani Darma Trg (Jurnal Scientia, 2024)
In this modern era, the need for environmentally friendly vehicles is increasing, along with the increasing awareness of the importance of protecting the environment from pollution. One solution that is increasingly popular is the use of two-wheeled electric vehicles. These electric vehicles utilize DC motors as the main drive. In this system, controlling the speed of the DC motor is an important aspect to ensure efficient and responsive performance. This study examines the implementation of Pulse Width Modulation (PWM) as a method of controlling the speed of a DC motor in two-wheeled electric vehicles. PWM is a technique that allows control of the power received by the motor by adjusting the width of the digital signal pulse. With this method, the speed of the motor can be controlled precisely without losing significant power efficiency. This study focuses on the design and implementation of a speed control system using PWM, as well as testing the performance of the system on two-wheeled electric vehicles. The results of the study show that the use of PWM as a method of controlling the speed of a DC motor in two-wheeled electric vehicles is able to provide a fast and accurate response to the desired speed changes. This system is also proven to be energy efficient and able to reduce the heat generated by the motor, thereby extending the life of the motor. Thus, the use of PWM in the DC motor speed control system in two-wheeled electric vehicles is an effective and efficient solution to improve the performance and reliability of electric vehicles.